Beryllium solubility and hydrolysis in dilute to concentrated CaCl2 solutions: thermodynamic description in cementitious systems - Çevirim-Papaioannou, Nese; Androniuk, Iuliia; Miron, George Dan; Altmaier, Marcus; Gaona, Xavier (Frontiers in Nuclear Engineering, 2023)
The solubility and hydrolysis of Be(II) was investigated from undersaturation conditions in alkaline, dilute to concentrated CaCl2 solutions (0.05-3.5 M). Experiments were performed with α-Be(OH)2(cr) under Ar atmosphere at T = (22 ± 2)°C. Aqueous Be speciation was further investigated by means of molecular dynamics (MD) calculations.For the most diluted CaCl2 systems (0.05 and 0.25 M), a solubility minimum is observed at pHm ≈ 9.5 (with [Be(II)] ≈ 10 -7 M), consistent with solubility data previously reported in NaCl and KCl solutions. Above this pHm, and at higher CaCl2 concentrations, a steep increase in the solubility with a slope of ~ +2 is observed, hinting towards the predominance of the moiety [Be(OH)4 2-] in the aqueous phase. In NaCl and KCl systems, this hydrolysis species prevails only above pHm ~ 13, thus supporting the formation of ternary complex/es Ca-Be(II)-OH(aq) in CaCl2 solutions. The analysis of solubility data in combination with MD calculations underpin the key role of the complex Ca2[Be(OH)4] 2+ in alkaline to hyperalkaline systems containing Ca.In combination with our previous work in NaCl-NaOH and KCl-KOH systems, complete chemical, thermodynamic and (SIT) activity models are derived for the first time for the system Be 2+ -Ca 2+ -Na + -K + -H + -Cl --OH --H2O(l). This model provides an accurate and robust tool for the evaluation of Be(II) solubility and speciation in a diversity of geochemical conditions, including source term calculations of beryllium in the context of repositories for nuclear waste disposal with a high cement inventory.